Clays and Clay Minerals, Vol.5 9, No.2, 147–164, 2011. - Cuadros, Javier; Dekov, Vesselin M.; Arroyo, Xabier; Nieto, Fernando (My University, 2011)
Clay processes, mineral reactions, and element budgets in oceans continue to be important topics for scientific investigation, particularly with respect to understanding better the roles of chemistry, formation mechanism, and input from hydrothermal fluids, seawater, and non-hydrothermal mineral phases.To that end, the present study was undertaken.Thre e samples of submarine metalliferous sediments of hydrothermal origin were studied to investigate the formation of smectite, usually Fe-rich, which takes place in such environments.The samples are from the historical collection returned by the British HMS Challenger expedition (1872-876) and kept at the Natural History Museum in London.The samples were collected from the vicinity of the Pacific-Antarctic Ridge and the Chile Ridge.The samples were analyzed by means of X-ray diffraction (XRD), chemical analysis, scanning electron microscopyenergy dispersive X-ray spectroscopy (SEM-EDX), infrared (IR), and transmission electron microscopyanalytical electron microscopy (TEM-AEM).After removal of biogenic calcite the samples appeared to consist mainly of two low-crystallinity phases mixed intimately: Fe/Mn (oxyhydr)oxides and a Si-Al-Mg- Fe phase of similar chemical characteristics to smectite and with variable proportions of the above elements, as indicated by XRD, IR, and SEM-EDX.In particular, analysis by XRD revealed the presence of highly disordered d-MnO2.The TEM-AEM analysis showed that Fe/MnOOH particles have Fe/Mn ratios in the range 25-0.2 and textures changing from granular to veil-like as the proportion ofMn increased. The smectite-like material has the morphology and chemistry of smectite, as well as 10-15 A ˚ lattice fringes. Selected area electron diffraction (SAED) patterns indicated a very poorly crystalline material: in some cases distances between diffraction rings corresponded to d values of smectite.The smectite composition indicated a main Fe-rich dioctahedral component with a substantialMg-rich trioctahedral component (total octahedral occupancy between 2.02 and 2.51 atoms per O10[OH]2).T he (proto-) smectite is interpreted to have formed within the metalliferous sediment, as a slow reaction between Fe/MnOOH, seawater (providing Mg), detrital silicates from the continent (providing Si and Al), and X-ray amorphous silica of hydrothermal origin that adsorbed on Fe/MnOOH phases and deposited with them.This material is possibly in the process of maturation into well crystallized smectite.
Smectite Formation In Submarine Hydrothermal Sediments: samples From The Hms Challenger Expedition (1872-1876)
gsccm59204-cua.pdf--901KB
Keywords: Periodicals; Geology; HMS Challenger; Metalliferous Sediments; Smectite Formation; TEM-AEM